2020
DOI: 10.3389/feart.2019.00328
|View full text |Cite|
|
Sign up to set email alerts
|

Variable Late Holocene 14C Reservoir Ages in Lake Bosten, Northwestern China

Abstract: Radiocarbon (14 C) dating has been widely used in paleoclimate reconstruction. However, the reliability of the 14 C age in lake sediments is sensitive to the 14 C reservoir effect, especially for a lake in arid regions. In this study, we evaluated the 14 C reservoir ages under different hydroclimatic conditions over the past ∼2300 years in Lake Bosten, northwestern China, by comparing with different dating results and with multi-proxy indices of a vertical-down sediment core collected in this lake. The 14 C re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The core was subsampled in situ at 0.5-cm intervals, and an accurate age model was established by 210 Pb-137 Cs dating method (Yan et al, 2019). Considering the great and variable old carbon effects that widely existed in lake sediments in northwest China (Zhou et al, 2020), we did not use the 14 C ages to augment our age model (Yan et al, 2019). The average sedimentation rate is ∼0.7 cm/year, and such a high sedimentation rate enables a potential reconstruction of a high-resolution dust storm history.…”
Section: Background and Methodsmentioning
confidence: 99%
“…The core was subsampled in situ at 0.5-cm intervals, and an accurate age model was established by 210 Pb-137 Cs dating method (Yan et al, 2019). Considering the great and variable old carbon effects that widely existed in lake sediments in northwest China (Zhou et al, 2020), we did not use the 14 C ages to augment our age model (Yan et al, 2019). The average sedimentation rate is ∼0.7 cm/year, and such a high sedimentation rate enables a potential reconstruction of a high-resolution dust storm history.…”
Section: Background and Methodsmentioning
confidence: 99%
“…Hydrological and climatic changes in northwest China could be the main factors responsible for the temporal changes in the 14 C reservoir ages of the lake sediments (Zhou et al 2009(Zhou et al , 2020. Studies of Lake Sugan and Lake Bosten showed that the reservoir effect was smaller during humid intervals, and significantly larger during dry intervals.…”
Section: Sources Of Toc In the Sediments Of Lake Kanasmentioning
confidence: 99%
“…The old carbon usually results from the following factors: disequilibrium in the 14 C exchange between water and the atmosphere, which leads to lower 14 C concentrations in the lake water (Druffel et al 1983); the influx of groundwater or surface runoff from watersheds with a limestone substrate, which introduces pre-aged carbon (Olsson 2009); biological utilization of dissolved inorganic carbon (DIC) in the lake water (Kwiecien et al 2008); an inherited reservoir effect from the introduction of sediments from the watershed (Frueh et al 2012); and the variable contribution of old terrestrial organic material eroded from catchment soils . The lake 14 C reservoir effect varies between different geographical units and over time (e.g., Hou et al 2012;Mischke et al 2013;Zhou et al 2014Zhou et al , 2021Zhou et al 2015;Zhou et al 2020), and assessing the reservoir effect is a priority in the 14 C dating of TOC and aquatic plant remains, to establish an accurate chronological framework for lake sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial variability of 14 C reservoir effects among different sites within individual lakes may be attributed to different degrees of 14 C exchange between aquatic dissolved inorganic carbon (DIC) and atmospheric CO 2 , and the lower reservoir ages in lake center result from more prolonged exchange of aquatic DIC with atmospheric CO 2 (Mischke et al., 2013). Moreover, the input of 14 C free carbon from carbon‐contained bedrocks may also partly contribute to the spatial variability in 14 C reservoir effects (Mischke et al., 2013; Zhou et al., 2020). Given that 14 C dating on lake sediments is restricted by the upper dating limit, availability of dating materials and reservoir effect across the NETP and its adjacent areas (C. Huang, Lai, et al., 2021; Lai et al., 2014), it has been suggested that the combination of OSL and 14 C dating enables accurate determination of lake 14 C reservoir ages and is capable of establishing reliable age models on longer timescales (An et al., 2018).…”
Section: Lake Sedimentary Records Of Dust Storms In Northwest Chinamentioning
confidence: 99%